Effect on Yield and Weed Dynamics in Maize (Zea mays L.) Based Intercropping Systems under Foothill Condition of Nagaland - Kithan, Lowrence; Longkumer, L. Tongpang (International Journal of Economic Plants, 2016)
To study the effect of maize based intercropping with legumes on crop yield and weed dynamics a field experiment was conducted at the experimental farm of School of Agricultural Sciences and Rural Development (SASRD) Nagaland University, Medziphema Campus, Nagaland under rainfed condition during 2015 and 2016 with treatments comprising of different row ratios i.e. (1:1), (1:2), (2:1) and (2:2) respectively of maize intercropped with perilla, sesame, ricebean and soybean along with sole crops of maize, perilla, sesame, ricebean and soybean. The experiment was laid in RBD with 3 replications and 21 treatments. Two years pooled mean of the data indicated that a sole crop was better than intercropping systems in respect of growth and yield attributing characters. Among the different intercropping systems paired rows (2:2) ratios of maize + soybean performed significantly better with highest pooled mean in terms of yield (1564.21 kg ha-1, 1567.10 kg ha-1) and LER (1.78, 1.78). On weed parameters minimum weed competition with regard to weed density was observed in paired rows (2:2) ratios of maize + sesame (145 m-2, 147.33 m-2), while for weed dry matter (g m-2) the treatment paired rows (2:2) ratios of maize + soybean (47.55 m-2, 52.33 m-2) showed lowest values. The common weed species identified were Borreria hispida, Amaranthus viridies, Ageratum conyzoides, Mimosa pudica, Cynodon dactylon, Digitaria sanguinalis, Imperata cylindrical and Cyperus rotundus. As for economics, paired rows (2:2) ratios of maize + soybean proved superior to all other treatments in net return (INR 1,42,612.6, INR 1,44,779.4), gross return (INR 1,72,612.6, INR 1,74,779.4) and B:C ratio (4.75 and 4.82).